Obstacles to Macrosecuritization of Global Threats: Cases of Nuclear Weapons and Climate Change - Ye. I. Uchaev; A. A. Kvartalnov (Сравнительная политика)
Despite the multitude of attempts to macrosecuritize nuclear weapons and climate change, none of them has succeeded so far. Existing studies struggle to convincingly explain these failures, which can be attributed both to the general neglect of unsuccessful cases of securitization and to the disparate, ad hoc nature of suggested explanations. Meanwhile, it has been little noticed that, as the discourse of existential threat implies judgements about the potential finitude of objects in time, there is a close link between securitization and temporality. By defining humanity’s time as potentially finite, the attempts to macrosecuritize nuclear weapons and climate change clash with the dominant indefinite temporality of modernity, as well as with the system of sovereign states that depends on indefinite temporality as its ideational condition of possibility. Consequently, macrosecuritizing moves, on the one hand, end up attempting to delegitimize and transform the system of sovereign states. On the other hand, the social structure of this system nudges the actors to ‘eternalize’ nuclear weapons and climate change, that is, to interpret them as compatible with humanity’s indefinite existence in the world. We demonstrate the workings of these ideational mechanisms during the discussions on international control of atomic energy in the 1940s and during the debates on international climate cooperation in 19871992. The cases show how, operating within a state-centric international political structure, policy makers are indeed inclined to ‘eternalize’ global existential threats.